Selected physical properties of solid biofuels - Vitázek Ivan; Vitázková Božena (Journal on Processing and Energy in Agriculture, 2012)
Rising fossil fuel prices and effort to limit production of gaseous emissions stimulate the increase in exploitation of renewable energy sources. In particular, solid biofuels are becoming widely used as a source of thermal energy. For their proper use it is essential to know their physical and chemical properties. The paper refers to a gravimetric method for determining the proportion of moisture, ash and combustible in selected solid biofuels. The quality offuel as an energy source depends on the quality of combustible and content of unexploitable substances - moisture and ash. Compared to solid fossil fuel the biomass has significantly higher proportion of volatile matter that burns with long and bright flame and affects the construction of combustion equipment itself as well as preparation and transportation of the biomass into the hearth. The results are processed graphically and illustrate the characterization of the examined fuel.